2013
DOI: 10.1017/s2045796013000462
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for improving well-being in people with a diagnosis of psychosis

Abstract: Background. Well-being is important for people with severe mental illness, such as psychosis. So far, no clear concept of well-being exists for this client group. A recent systematic review and narrative synthesis developed a static framework of well-being components. The present study aims to validate the static framework and to illuminate the processes by which well-being is experienced by people with psychosis. Methods. Semi-structured interviews were conducted with 23 service users with psychosis exploring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…These definitions bring concepts of health and well-being closely together but, as in the recovery literature, allowed for individuals with significant psychiatric 'disorders' to achieve a sense of well-being. 56,57 It is well established that attention is needed to improve the physical health of people with SMI 58 because of consistent findings that their health was poorer than the general population. 31 Health issues include a higher prevalence of cardiovascular disease, 59 diabetes, 60 obesity 61 and a shorter lifespan, estimated at 13-30 years less than the general population.…”
Section: Health and Well-beingmentioning
confidence: 99%
“…These definitions bring concepts of health and well-being closely together but, as in the recovery literature, allowed for individuals with significant psychiatric 'disorders' to achieve a sense of well-being. 56,57 It is well established that attention is needed to improve the physical health of people with SMI 58 because of consistent findings that their health was poorer than the general population. 31 Health issues include a higher prevalence of cardiovascular disease, 59 diabetes, 60 obesity 61 and a shorter lifespan, estimated at 13-30 years less than the general population.…”
Section: Health and Well-beingmentioning
confidence: 99%
“…An adaptation of standard 14-session PPT (WELLFOCUS PPT) has been developed for people with psychosis Schrank, Riches, et al, 2013) and tested in a randomized controlled trial (Schrank, Riches, et al, 2014), which was found to improve specific aspects of well-being, including overall symptomatology and depression. The aim of this study was to investigate service user experience of therapy components in WELLFOCUS PPT.…”
mentioning
confidence: 99%
“…Moreover, study quality appears to be associated with significant results, as those with moderate quality were most likely to significantly improve and maintain the well-being of the community dwelling well elderly than those of poorer quality. This is similar to other areas of psychology and points to the necessity of conducting more carefully designed RCTs in the future (Schrank et al 2014). For future research, poor quality studies should be excluded for a meta-analysis due to the quality of individual study influences the confidence intervals around the effect size (Boland et al 2014).…”
Section: Discussionmentioning
confidence: 88%